Vietnam: Business and investment opportunities - Leong, Tan Cheng (Cassia Communications, 1993)
First series of resource book is offered not as an exhaustive authority on the selected market but as a useful, convenient, practical reference guide from which inferences may be drawn when critical business decisions have to be made.